THE EFFECT OF CELEBRITY SUPPORT AND BRAND IMAGE ON THE PURCHASE DECISION OF FACE CLEANSER PRODUCTS IN MEDAN CITY - Ardianto, Ryan; Astuti, Rini (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2022)
The purpose of this study was to determine and analyze the influence of celebrity endorsements and brand image on purchasing decisions for Garnier Men facial cleansing products in Medan. The research used in this study is a quantitative approach. In determining the sample, this study uses a saturated technique (census) where all the population is used as a sample of 100 people. The data collection technique used in this study is a questionnaire (questionnaire), to analyze the data and information needed, the authors use data techniques where hypothesis testing is used after going through stages such as distributing questionnaires. To test the quality of the questionnaire using validity and reliability tests. The analytical technique used in this study is quantitative data analysis techniques. The results of this study indicate that there is a positive and significant influence between the variablesCelebrity Support on Purchase Decisions, there is a positive and significant influence between Brand Image variables on Purchase Decisions for Garnier Men facial cleansing products in Medan City.